Monitoring the Kinase Activity of Heme-Based Oxygen Sensors and Its Dependence on O2 and Other Ligands Using Phos-Tag Electrophoresis - Vávra, Jakub; Sergunin, Artur; Shimizu, Toru; Martínková, Markéta (Methods in molecular biology (Clifton, N.J.), 2023)
The nonradioactive method, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) in the presence of Phos-tag (Phos-tag electrophoresis), is used to evaluate a kinase autophosphorylation and/or phosphotransfer reaction from a kinase/ATP to its protein substrate. This method outperforms radioisotope methods using [32P]ATP for detecting trace amounts of phosphorylated protein in fresh protein preparations. Phos-tag electrophoresis has been used to perform detailed analyses of the kinase activity of a heme-based oxygen sensor-specifically, a globin-coupled histidine kinase from the soil bacterium Anaeromyxobacter sp. Fw109-5 (AfGcHK).
Keywords: Ligand binding; Ligand-dependent kinase activity; proteiny; adenosintrifosfát; Oxygen; hem; ligandy; Phosphotransfer reaction; Heme-based oxygen sensors; Ligands; Bacteria; elektroforéza v polyakrylamidovém gelu; Kinase activity; Electrophoresis, Polyacrylamide Gel; kyslík; Phos-tag electrophoresis; Adenosine Triphosphate; Heme; Autophosphorylation reaction; Proteins